2010
DOI: 10.3899/jrheum.100455
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Small-Vessel Inflammation in Patients with Giant Cell Arteritis: Clinical Course and Preliminary Immunohistopathologic Characterization

Abstract: A significant number of patients with clinical features of GCA demonstrated isolated TSVI. Differences in the clinical presentation and cellular composition suggest that TSVI may represent a subset of GCA and should be considered in the interpretation of temporal artery biopsies and treatment decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 15 publications
3
23
1
1
Order By: Relevance
“…Some studies have suggested that SVV should not be construed as histologic evidence of GCA because of the lack of a clinical association (5, 8, 11). Other studies have considered SVV to be characteristic of a particular subset of GCA or associated with a systemic necrotizing vasculitis (3, 4, 6, 7). Finally, SVV has also been reported in nonvasculitic conditions such as infections and tumors (5, 8).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have suggested that SVV should not be construed as histologic evidence of GCA because of the lack of a clinical association (5, 8, 11). Other studies have considered SVV to be characteristic of a particular subset of GCA or associated with a systemic necrotizing vasculitis (3, 4, 6, 7). Finally, SVV has also been reported in nonvasculitic conditions such as infections and tumors (5, 8).…”
Section: Discussionmentioning
confidence: 99%
“…After histologic review, biopsy specimens were classified into 1 of the following 4 categories: 1) biopsy specimens with classic GCA (if histologic examination of the temporal artery biopsy showed transmural infiltration predominantly of lymphomononuclear cells in the temporal artery wall, with or without giant cells) (2); 2) biopsy specimens without evidence of inflammation of the temporal artery and the surrounding connective tissue; 3) biopsy specimens with SVV surrounding an uninflamed temporal artery according to the criteria proposed by Chatelain et al (aggregates of mononuclear inflammatory cells around capillaries located in the connective tissue surrounding the adventitia) (3); and 4) biopsy specimens with VVV in the adventitia as the only lesion observed in the temporal artery. According to the study by Belilos et al (4), the external limit of the temporal artery adventitia is histologically defined as the site of transition from densely packed collagen with elastic fibers to loose collagen lacking elastic fibers in the surrounding connective tissue (4). In the SVV group, inflammation was external to the temporal artery adventitia.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…10,[22][23][24] Sometimes, these incomplete findings are the only abnormality observed, but in other instances further sectioning reveals more characteristic features. 10,[22][23][24] However, incomplete findings may be equivocal: involvement of periadventitial vessels can be seen in other vasculitides affecting medium or small vessels (polyarteritis nodosa or anti-neutrophil cytoplasmic antibody (ANCA) associated vasculitis). 10,25 Furthermore, slight inflammatory changes in small vessels or vasa vasorum can be seen in severe chronic infections such as endocarditis or in malignancies, possibly as a result of pattern recognition-mediated activation of endothelial cells or systemic release of inflammatory mediators.…”
Section: Improving Temporal Artery Biopsy Sensitivitymentioning
confidence: 92%
“…Morphological evidence of the disease will then provide proof that both diagnosis and treatment were appropriate. Finally, although scalp necrosis, brow droop, chronic skin ulceration and stroke have been described, TAB is associated with low-morbidity (210). As emphazised earlier, an ultrasound should be performed to identify the most suitable location fo biopsy.…”
Section: Temporal Artery Biopsymentioning
confidence: 99%